Educational Game Tools to Improve the Language Development of Children Aged 5-6 Years - Rahmita, Nelly; Khadijah, Khadijah; Mutiara, Yolanda (Universitas Islam Negeri Raden Intan Lampung, 2023)
The lack of teacher creativity in using educational game tools has limited costs and a lack of teacher knowledge in early childhood education causes a learning medium. This research aims to determine educational game tools that can improve the language development of children aged 5-6 years. The research methodology used was library research. The research results show that educational game tools are not only able to improve language development but other developments are also stimulated, such as children's cognitive and social development. Data obtained from relevant previous research results through game tools, such as toy telephones (can telephones), word cards (flashcards), hand puppets, and posters, can improve the development of children aged 5-6. Therefore, this research makes it easier for readers to learn about educational game tools that can enhance language development in early childhood and can be used as a reference for PAUD educational institutions that need them.